Negative pole piece, electrochemical device and preparation method of negative pole piece

By designing a negative electrode active material layer with a two-layer structure in the negative electrode sheet, adjusting the structural stability parameters and hardness distribution, the problem of insufficient fast charging and cycling performance of lithium-ion batteries is solved, and the overall performance of the battery is improved.

CN119230769APending Publication Date: 2024-12-31AESC DYNAMICS TECHNOLOGY (HEBEI) LTD +4
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310797433.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The prior art is difficult to effectively optimize the dynamic performance of the negative electrode plate, resulting in limited fast charging and cycling performance of lithium-ion batteries, and lacks methods to improve the cell performance at the electrode plate level.

Method used

By designing a negative electrode active material layer with a two-layer structure in the negative electrode sheet, adjusting the structural stability parameter ratio S1/S2 of the first active material layer and the second active material layer, combining the appropriate hardness distribution and compaction density to form a low A structure with tortuosity, high orientation and rich pores.

Benefits of technology

It significantly improves the fast charging, circulation and storage performance of lithium-ion batteries, and achieves the dynamic balance and structural stability of the negative electrode sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230769A_ABST
    Figure CN119230769A_ABST
Patent Text Reader

Abstract

The invention provides a negative pole piece, an electrochemical device and a preparation method of the negative pole piece, and belongs to the technical field of secondary batteries, and the negative pole piece comprises a current collector and a negative active material layer. Wherein the negative electrode active material layer is at least located on one surface of the current collector, the negative electrode active material layer comprises a first active material layer and a second active material layer, and the first active material layer and the second active material layer are arranged in a stacked mode in the direction close to the current collector; the structural stability parameter ratio S1 / S2 of the first active material layer to the second active material layer satisfies 0.01-10.0. According to the negative pole piece, the electrochemical device and the preparation method of the negative pole piece, the negative pole active material layer forms a structure with gradient decreasing hardness along the direction close to the current collector by adjusting the structural stability parameter of the double-layer structure in the negative pole active material layer, so that the pore distribution and the structural stability of the negative pole active material layer are effectively optimized; and the fast charging, circulating and storage performances of the lithium ion battery are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a negative electrode sheet, an electrochemical device and a method for preparing the negative electrode sheet. Background Art

[0002] In traditional lithium-ion battery systems, the charging capacity, cycle performance, processing performance and safety performance of lithium-ion batteries are largely determined by the negative electrode. At present, the optimization strategy of negative electrode plates usually focuses on compaction density, surface density, active material ratio, etc. However, as the performance of battery cells gradually approaches the bottleneck, we need to refine the influence of the electrode layer on the performance of the battery cell, so as to more effectively improve the performance of the corresponding battery cell from the intrinsic level.

[0003] At present, there is no more room for simply adjusting the compaction density, surface density, and active material ratio of the negative electrode material to optimize the fast charging and cycling performance of the battery cell. It is necessary to reasonably consider the physical and chemical characteristics of the negative electrode plate, and optimize the distribution and orientation of particles and pores in the negative electrode active material layer by comprehensively adjusting the material ratio, hardness distribution, and compaction density of the negative electrode active material layer, thereby improving the kinetic balance of the negative electrode plate, and then optimizing the fast charging and cycling performance of the lithium-ion battery.

[0004] Therefore, it is necessary to design a negative electrode sheet, an electrochemical device and a method for preparing the negative electrode sheet to solve the above problems. Summary of the invention

[0005] In view of the above shortcomings of the prior art, the present invention provides a negative electrode plate, an electrochemical device and a method for preparing a negative electrode plate, which comprehensively adjusts the material ratio, hardness distribution and compaction density of the negative electrode active material layer in the negative electrode plate, thereby improving the technical problem that the prior art is difficult to comprehensively optimize the distribution and orientation of particles and pores in the negative electrode active material layer and cannot effectively balance the dynamic performance of the negative electrode plate.

[0006] To achieve the above-mentioned object and other related objects, the present invention provides a negative electrode plate, which includes a current collector and a negative electrode active material layer.

[0007] Wherein, the negative electrode active material layer is located on at least one side of the current collector, and the negative electrode active material layer includes a first active material layer and a second active material layer, and the first active material layer and the second active material layer are stacked in a direction close to the current collector; and the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer satisfies 0.01-10.0.

[0008] In an example of the present invention, the negative electrode material in the negative electrode active material layer includes graphite material.

[0009] In an example of the present invention, the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer satisfies 0.1-5.0.

[0010] In an example of the present invention, the structural stability parameter S1 of the first active material layer is 3-16.

[0011] In one example of the present invention, the negative electrode active material layer satisfies Wherein, τ is the tortuosity of the negative electrode active material layer, ε is the porosity of the negative electrode active material layer, P is the compaction density of the negative electrode active material layer, V OI It is the stacking orientation degree of the negative electrode material particles in the negative electrode active material layer.

[0012] In one example of the present invention, the negative electrode active material layer satisfies

[0013] In one example of the present invention, the compaction of the negative electrode active material layer is 1.65-1.75 g / cm 3 .

[0014] On the other hand, the present invention provides a method for preparing a negative electrode plate, which comprises the following steps: mixing a first negative electrode material with a binder, a conductive agent and a thickener to form a slurry to obtain a first active material layer slurry; mixing a second negative electrode material with a binder, a conductive agent and a thickener to form a slurry to obtain a second active material layer slurry; coating the second active material layer slurry and the first active material layer slurry on at least one side of a current collector in sequence, and drying, compacting, die-cutting and punching after coating to obtain a negative electrode plate; wherein the hardness of the first negative electrode material is higher than that of the second negative electrode material.

[0015] In an example of the present invention, the structural stability parameter ratio S1 / S2 of the first negative electrode material and the second negative electrode material satisfies 0.01-10.0.

[0016] In one example of the present invention, the average particle size Dv50 of the first negative electrode material is 11-17 μm, and the average particle size Dv50 of the second negative electrode material is 16-19 μm.

[0017] The present invention also provides an electrochemical device, which includes a positive electrode plate, a separator, an electrolyte, and a negative electrode plate described in any one of the above examples.

[0018] The negative electrode sheet, electrochemical device and method for preparing the negative electrode sheet in the present invention adjust the structural stability parameters of the double-layer structure in the negative electrode active material layer to form a structure with a decreasing hardness gradient in the direction close to the current collector, thereby effectively optimizing the pore distribution and structural stability of the negative electrode active material layer, and forming a negative electrode sheet with low tortuosity, high orientation and rich pores during compaction, thereby further improving the fast charging, cycling and storage performance of lithium-ion batteries. Therefore, the present invention effectively overcomes some practical problems in the prior art and has high utilization value and use significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 Schematic diagram of the structure of the negative electrode plate in one embodiment of the present invention.

[0021] Figure 2 Schematic diagram of a process for preparing a negative electrode sheet in one embodiment of the present invention.

[0022] Component number description

[0023] 100 , current collector; 200 , negative electrode active material layer; 210 , first active material layer; 220 , second active material layer. DETAILED DESCRIPTION

[0024] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.

[0025] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" etc. used in this specification are only for the convenience of description and are not intended to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be regarded as the scope of implementation of the present invention.

[0026] In this specification, the structural stability parameter S of the negative electrode material is an index of the structural stability of the secondary particles of the material (a single particle is defined as 100.0). For the specific definition, please refer to the test method of the structural stability parameter below.

[0027] The tortuosity τ of the negative electrode sheet is defined as: the ratio of the actual length of the pores in the negative electrode active material layer of the negative electrode sheet to the shortest distance in the direction perpendicular to the current collector of the negative electrode active material layer.

[0028] The porosity ε of the negative electrode sheet is defined as: the ratio of the pore volume in the porous negative electrode material to the apparent volume (or total volume) of the porous negative electrode material in the negative electrode sheet, generally expressed as a percentage.

[0029] Orientation degree V of negative electrode OI It indicates the stacking orientation degree of the negative electrode material particles in the negative electrode sheet, and is defined as the intensity ratio of the I004 / I110 peak in the XRD diffraction of the negative electrode material in the negative electrode sheet.

[0030] The average particle size Dv50 of a material can be defined as the particle size corresponding to 50% of the volume accumulation in the particle size distribution curve of the particles. The average particle size Dv50 can be measured, for example, by a laser diffraction method. The laser diffraction method is generally capable of measuring particle sizes from the submicron range to several millimeters, thereby obtaining highly reproducible and high-resolution results.

[0031] The present invention provides a negative electrode plate, which is used to participate in the production of an electrochemical device. The electrochemical device usually includes a positive electrode plate, a negative electrode plate, an electrolyte, a diaphragm, and corresponding connecting accessories and circuits. The positive and negative electrode materials in the positive and negative electrode plates can deintercalate lithium ions to achieve energy storage and release, the electrolyte is a carrier for the transmission of lithium ions between the positive and negative electrodes, and the diaphragm can pass lithium ions but is not conductive, thereby separating the positive and negative electrodes to prevent short circuits. The positive and negative electrode plates usually play a decisive role in key performance factors such as the energy storage function of the lithium battery, the energy density of its battery cell, the cycle performance and safety.

[0032] like Figure 1As shown, the negative electrode sheet provided by the present invention includes a current collector 100 and a negative electrode active material layer 200, and the negative electrode active material layer 200 is located on at least one surface of the current collector 100. Specifically, the current collector 100 has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer 200 is arranged on any one or both of the two surfaces of the current collector 100. Among them, the current collector 100 can be made of a material with good conductivity and mechanical strength, which plays the role of conduction and current collection. In some embodiments, the current collector 100 can be made of copper foil.

[0033] like Figure 1 As shown, the negative electrode active material layer 200 includes a first active material layer 210 and a second active material layer 220. In the negative electrode active material layer 200, the first active material layer 210 and the second active material layer 220 are stacked in a direction close to the current collector 100, the second active material layer 220 is arranged on the surface of the current collector 100, and the first active material layer 210 is arranged on the second active material layer 220.

[0034] Among them, since the first active material layer 210 and the second active material layer 220 are stacked in the direction close to the current collector 100 in the negative electrode active material layer 200, the hardness of the material of the negative electrode active material layer 200 after compaction can be made to decrease gradually in the direction close to the current collector 100 by adjusting the ratio of the structural stability parameter S of the first active material layer 210 and the second active material layer 220. The material structure of the negative electrode active material layer 200, which is tight in the direction close to the current collector 100 and loose in the bottom, is more conducive to forming a reasonable distribution of particles and pores during the compaction process, thereby increasing the structural stability and pore richness of the negative electrode sheet.

[0035] In some embodiments, in the negative electrode active material layer, the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer materials satisfies 0.01-10.0, so that a negative electrode active material layer with appropriate overall hardness and rich porosity can be formed on the negative electrode sheet.

[0036] Among them, when the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer material meets 0.01-10.0, the pore distribution of the negative electrode sheet is reasonable, the structural stability is high, the porosity ε of the negative electrode sheet is 15%-30%, and the tortuosity τ of the negative electrode sheet is 3-6. When the ratio of S1 / S2 is too high, it is beneficial to improve the pore richness and hardness of the negative electrode sheet, but it will greatly reduce the structural stability and compaction density of the negative electrode sheet; when the ratio of S1 / S2 is too low, it will lead to a decrease in the pore richness of the negative electrode sheet, causing the porosity ε of the negative electrode sheet to decrease to less than 15%, and the pore tortuosity τ to increase to more than 6, which will cause the kinetic performance of the negative electrode sheet to deteriorate, and the charge and discharge performance of the secondary battery to decline significantly.

[0037] In some embodiments, in the negative electrode active material layer, the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer materials satisfies: 0.01≤S1 / S2≤3, 0.1≤S1 / S2≤3, 0.1≤S1 / S2≤5, 1≤S1 / S2≤7, 3≤S1 / S2≤7, 3≤S1 / S2≤8, 3≤S1 / S2≤10, 5≤S1 / S2≤7 or 5≤S1 / S2≤10, etc.

[0038] In some preferred embodiments, in the negative electrode active material layer, the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer material satisfies 0.01-5.0. In the negative electrode active material layer of the negative electrode sheet, the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer material is within an appropriate range, which is more conducive to improving the porosity, compaction density and structural stability of the negative electrode sheet and reducing the pore tortuosity of the negative electrode sheet.

[0039] In some embodiments, on the basis that the negative electrode plate satisfies the above conditions, the structural stability parameter S1 of the first active material layer material is 3.0-16.0, for example, 3.0, 3.7, 5.0, 7.4, 8.0, 8.3, 10.0, 10.4, 13.4, 15.1, 15.6 or 16.0; the structural stability parameter S2 of the second active material layer material can be any value that satisfies the structural stability parameter ratio range (0.01≤S1 / S2≤10.0), for example, the structural stability parameter S2 of the second active material layer material can be any value that satisfies the stability parameter ratio range of 1.0-100.0.

[0040] In some embodiments, by adjusting the overall compaction density and interlayer structure parameters of the negative electrode sheet, the negative electrode active material layer satisfies: Within this range, the negative electrode sheet forms a negative electrode active material layer with low tortuosity, high orientation and high porosity, thereby improving the fast charging capability of the double-layer negative electrode active material layer in the negative electrode sheet; wherein τ is the tortuosity of the negative electrode active material layer, ε is the porosity of the negative electrode active material layer, P is the compaction density of the negative electrode active material layer, V OI It is the stacking orientation degree of the negative electrode material particles in the negative electrode active material layer.

[0041] In some embodiments, the negative electrode active material layer satisfies: or

[0043] In some preferred embodiments, the negative electrode active material layer of the negative electrode sheet satisfies Among them, when the negative electrode active material layer of the negative electrode sheet When the parameters are within the above range, it is more conducive to improving both the fast charging and cycle performance of the secondary battery.

[0044] The inventors have conducted in-depth research and found that when the negative electrode plate of the present application satisfies the above conditions and optionally satisfies one or more of the following design conditions, the performance of the secondary battery can be further improved.

[0045] In some preferred embodiments, the compaction density P of the negative electrode sheet is 1.65-1.75 g / cm 3 , for example, 1.65 g / cm 3 , 1.67g / cm 3 , 1.70g / cm 3 、1.73g / cm 3 or 1.75g / cm 3 .

[0046] In some preferred embodiments, the porosity ε of the negative electrode sheet is 15%-30%, for example, 15%, 17%, 20%, 22%, 25%, 27%, 29% or 30%.

[0047] In some preferred embodiments, the tortuosity τ of the negative electrode plate is 3-5, for example, 3.0, 3.3, 3.37, 3.5, 3.6, 3.64, 3.8, 4.0, 4.2, 4.5, 4.7 or 5.0.

[0048] In some preferred embodiments, the orientation degree V of the negative electrode sheet OI is 14-24, for example, 14, 16, 18, 21, 22, 23 or 24.

[0049] In some embodiments, the negative electrode material in the negative electrode active material layer includes a core and a coating layer, the core includes a graphite material, the coating layer is coated on the surface of the core, and the coating layer includes amorphous carbon.

[0050] In the above embodiments, the graphite material includes natural graphite, artificial graphite and graphitized carbon. Preferably, the graphite material can be artificial graphite.

[0051] In the above embodiment, the amorphous carbon coating layer can be formed by carbonizing an organic carbon source. For example, the organic carbon source can be selected from high molecular polymers, such as coal tar, petroleum asphalt, phenolic resin and other high molecular materials.

[0052] Amorphous carbon has a disordered structure and a high interlayer spacing. Therefore, the use of amorphous carbon to coat the core material can make the active ions diffuse faster in the negative electrode material particles, thereby improving the fast charging ability of the negative electrode material. At the same time, the amorphous carbon coating layer can also protect the core, greatly reducing the peeling of the graphite layer caused by the co-embedding of the core material due to the solvent, so that the negative electrode material has a higher structural stability. Therefore, the negative electrode material can have a higher capacity and cycle life.

[0053] In addition, it should be noted that the negative electrode active material layer also includes a binder and a conductive agent. The binder is selected from at least one of polyimide, styrene-butadiene rubber, polyacrylic acid, polyvinylidene fluoride, sodium carboxymethyl cellulose, and lithium carboxymethyl cellulose. The conductive agent is selected from at least one of carbon black, SP, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene.

[0054] See also Figure 2 The present invention provides a method for preparing a negative electrode sheet, comprising the following steps:

[0055] S1, mixing the first negative electrode material with a binder, a conductive agent and a thickener to prepare a slurry to obtain a first active material layer slurry;

[0056] S2, mixing the second negative electrode material with a binder, a conductive agent and a thickener to form a slurry to obtain a second active material layer slurry;

[0057] S3. Coat the second active material layer slurry and the first active material layer slurry on at least one side of the current collector in sequence to form a negative electrode active material layer on the current collector (in the negative electrode active material layer, the second active material layer is coated on the current collector, and the first active material layer is coated on the second active material layer). After coating, dry, compact, die-cut and punch to obtain a negative electrode sheet.

[0058] In the preparation method of the negative electrode sheet, the first negative electrode material and the second negative electrode material with suitable physical parameters are selected to prepare the first active material layer slurry and the second active material layer slurry, and the design of the interlayer structure of the negative electrode active material layer is realized by sequentially coating the second active material layer slurry and the first active material layer slurry on the current collector. After drying and compacting, the negative electrode active material layer with the interlayer structure can be reasonably spaced and arranged with different particle sizes inside, so as to form a pore structure with abundant quantity and high orientation between the particles, thereby further improving the structural stability and rationality of pore distribution of the negative electrode active material layer on the basis of the dynamics of the selected negative electrode material.

[0059] In steps S1 and S2, the first negative electrode material and the second negative electrode material used are both negative electrode materials with a core of graphite material and a coating of amorphous carbon. The graphite material is selected from one or more of natural graphite, artificial graphite and graphitized carbon, and the amorphous carbon can be formed by carbonizing an organic carbon source on the graphite material. For example, the organic carbon source can be selected from polymers such as coal tar, petroleum asphalt, phenolic resin and other polymer materials.

[0060] In step S1 and step S2, the binder is selected from at least one of polyimide, styrene-butadiene rubber, polyacrylic acid, polyvinylidene fluoride, sodium carboxymethyl cellulose, and lithium carboxymethyl cellulose, among which styrene-butadiene rubber is preferred; the conductive agent is selected from at least one of carbon black, SP, single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene, among which carbon black is preferred; and the thickener is sodium carboxymethyl cellulose (CMC).

[0061] In some embodiments, in step S1 and step S2, the structural stability parameter ratio S1 / S2 of the selected first negative electrode material and the second negative electrode material satisfies 0.01-10.0. Under this structural parameter, the hardness of the first negative electrode material is higher than that of the second negative electrode material. The second negative electrode material and the first negative electrode material using this structural stability parameter ratio range form a double-layer structure of the negative electrode active material layer on the current collector in the direction away from the current collector, and the internal hardness of the negative electrode active material layer after compaction processing can be made to show a gradient downward trend in the direction close to the current collector, thereby increasing the structural stability of the negative electrode sheet and the rationality of the pore distribution.

[0062] Furthermore, in some preferred embodiments, the structural stability parameter ratio S1 / S2 of the selected first negative electrode material and the second negative electrode material satisfies 0.1-5.0.

[0063] In some embodiments, in step S1 and step S2, a first negative electrode material with an average particle size Dv50 of 11-17 μm is selected to prepare a first active material layer slurry, for example, a first negative electrode material with an average particle size Dv50 of 11 μm, 11.2 μm, 12.2 μm, 13 μm, 13.3 μm, 13.7 μm, 14 μm, 14.5 μm, 15 μm, 15.6 μm, 16 μm, 16.2 μm or 17 μm is selected. A negative electrode material; a second negative electrode material having an average particle size Dv50 of 16-19 μm is selected to prepare a second active material layer slurry, for example, a second negative electrode material having an average particle size Dv50 of 16 μm, 16.7 μm, 17 μm, 17.5 μm, 18 μm, 18.3 μm, 18.7 μm or 19 μm is selected; and the average particle size Dv50 of the second negative electrode material is selected to be higher than the average particle size Dv50 of the first negative electrode material.

[0064] In this embodiment, in step S3, a double-layer structure of a negative electrode active material layer is formed by coating the second active material layer slurry and the first active material layer slurry onto the current collector. The negative electrode active material layer has a double-layer structure with a similar average particle size Dv50, and the average particle size Dv50 of the particles of the outer first active material layer in the double-layer structure is relatively low, and the average particle size Dv50 of the particles of the inner second active material layer is relatively high.

[0065] Since the interlayer structure of the negative electrode active material layer is generally low in the average particle size Dv50 of the outer layer particles and high in the average particle size Dv50 of the inner layer particles, the gaps between the inner layer material particles in the negative electrode active material layer are large, and the gaps between the outer layer material particles are small. Therefore, during the compaction of the negative electrode sheet, the material particles of the first active material are compacted and embedded between the material particles of the second active material layer, so that the particles in the negative electrode active material layer form a spaced arrangement with a high space utilization rate. A large number of spaced particles are easy to take into account the improvement of the orientation and porosity of the negative electrode active material layer. In addition, since the average particle size Dv50 of the particles in the double-layer structure of the negative electrode active material layer is relatively close, the pore structure formed between the particles after compaction has a higher orientation and a lower tortuosity.

[0066] Therefore, in step S3, on the basis of coating the interlayer structure of the negative electrode active material layer on the current collector, the compaction density of the negative electrode active material layer is adjusted by compaction to make the negative electrode sheet The temperature is between 6.5 and 80 to form a negative electrode sheet with low tortuosity, high orientation and rich pores, thereby effectively improving the fast charging and cycle performance of the negative electrode sheet.

[0067] In step S3, a double-cavity coating die is used to pass the first active material layer slurry into the upper cavity of the double-cavity coating die, and the second active material layer slurry is passed into the lower cavity of the double-cavity coating die. Then, the first active material layer slurry and the second active material layer slurry in the upper cavity and the lower cavity of the double-cavity coating die are mixed in a weight ratio of 1:1, and the coating weight is 105 g / m 2 The parameters are uniformly coated on the surfaces of both sides of the current collector, so as to form a negative electrode active material layer with a double-layer structure of a second active material layer and a first active material layer stacked in a direction away from the current collector on the surface of the current collector; after coating, the negative electrode active material layer on the current collector is dried, compacted, die-cut and punched to obtain a negative electrode sheet.

[0068] The present invention also provides an electrochemical device, the electrochemical device comprises the negative electrode sheet described in any of the above embodiments of the present invention or the negative electrode sheet prepared by the preparation method described in any of the above embodiments, the electrochemical device is such as a secondary lithium-ion battery, the battery comprises a positive electrode sheet, a negative electrode sheet, a diaphragm disposed between the positive electrode sheet and the negative electrode sheet, and an electrolyte. Among them, the positive and negative electrode materials on the positive and negative electrode sheets can deintercalate lithium ions to achieve energy storage and release, the electrolyte is a carrier for lithium ions to be transmitted between the positive and negative electrodes, and the diaphragm can pass lithium ions but is not conductive, thereby separating the positive and negative electrodes to prevent short circuits.

[0069] The positive electrode sheet, separator and electrolyte can be made of conventional materials and preparation methods in the art, as an example:

[0070] The preparation process of secondary lithium-ion batteries is as follows:

[0071] Preparation of positive electrode sheet: The ternary positive electrode material (LiNi 0.8 Co 0.1 Mn 0.1 O2), conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1.5:1.5, and a solvent N-methylpyrrolidone (NMP) is added, and the mixture is stirred and mixed to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is prepared through drying, cold pressing, slitting and other processes. Among them, the conductive agent can also be selected from: at least one of acetylene black, carbon nanotubes, graphene, VGCF and other conductive materials; the binder can also be selected from: at least one of PVDF, PTFE and the like.

[0072] The negative electrode sheet preparation process is as mentioned above.

[0073] Preparation of diaphragm: A PE porous membrane with a thickness of 11 μm is selected as the diaphragm. The thickness of the diaphragm is 9 μm to 18 μm; the air permeability is 180 s / 100 mL to 380 s / 100 mL; the porosity is 30% to 50%

[0074] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are uniformly mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0075] Assemble the battery: stack the prepared positive electrode sheet, separator, and negative electrode sheet in sequence, so that the separator is placed between the positive and negative electrode sheets to play a role of isolation. Then wrap it with aluminum plastic film, inject the above-prepared electrolyte after drying, and finally prepare a soft-pack battery (i.e., lithium-ion battery) with a capacity of 1Ah after packaging, standing, and formation.

[0076] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available products or can be prepared by conventional methods in the art.

[0077] Example 1

[0078] This embodiment provides a negative electrode plate. The structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer in the negative electrode active material layer of the negative electrode plate is 1.6. It is 37.0.

[0079] The method for preparing the negative electrode sheet comprises:

[0080] S1, the first negative electrode material is mixed with a binder of styrene-butadiene rubber, sodium carboxymethyl cellulose and a conductive agent of carbon black (purchased from Swiss Graphite and Carbon Company, model Super P, referred to as SP) in a weight ratio of 94.7:2.5:1.8:1, 82 parts by weight of water are added to 100 parts by weight of the mixture, and the mixture is stirred to obtain a first active material layer slurry; wherein the first negative electrode material is an artificial graphite material having a structural stability parameter S1 of 3.7 and an average particle size Dv50 of 15.6 μm;

[0081] S2, the second negative electrode material is mixed with a binder of styrene-butadiene rubber, sodium carboxymethyl cellulose and a conductive agent of carbon black (purchased from Swiss Graphite and Carbon Company, model Super P, referred to as SP) in a weight ratio of 94.7:2.5:1.8:1, 82 parts by weight of water are added to 100 parts by weight of the mixture, and the mixture is stirred to obtain a second active material layer slurry; wherein the second negative electrode material is an artificial graphite material having a structural stability parameter S2 of 2.3 and an average particle size Dv50 of 16.7 μm;

[0082] S3, using a double-cavity coating die (manufactured by Mannster, model BG01A-400-30B), the first active material layer slurry is passed into the upper cavity of the double-cavity coating die, and the second active material layer slurry is passed into the lower cavity of the double-cavity coating die, and then the first active material layer slurry and the second active material layer slurry in the upper cavity and the lower cavity of the double-cavity coating die are mixed in a weight ratio of 1:1, and the coating weight is 105g / m 2 The parameters are uniformly coated on the surfaces of both sides of the 8μm copper foil current collector; then, the current collector is dried and roll-pressed so that the compaction density of the negative electrode active material layer on the current collector is 1.65g / m 3 , and finally the negative electrode sheet is obtained through die cutting and punching.

[0083] This embodiment also uses the above-mentioned negative electrode plate to prepare a secondary lithium ion battery. The preparation method of the secondary lithium ion battery is as follows:

[0084] (1) Preparation of positive electrode sheet:

[0085] The ternary positive electrode material (LiNi 0.8 Co 0.1 Mn 0.1 O2), conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1.5:1.5, and solvent N-methylpyrrolidone (NMP) is added, and the mixture is stirred thoroughly to obtain a positive electrode slurry; the mixture is stirred under the action of a vacuum mixer until the system is uniform and transparent to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on a 16μm aluminum foil current collector, and then the aluminum foil current collector is dried at room temperature and transferred to an oven at 80℃~120℃ for 6h, and then cold pressed and cut to obtain a positive electrode sheet.

[0086] (2) The negative electrode sheet preparation process is shown in this embodiment.

[0087] (3) Preparation of electrolyte:

[0088] In an argon atmosphere glove box with a water content of <10ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are uniformly mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0089] (4) Diaphragm preparation:

[0090] A PE porous membrane with a thickness of 11 μm was selected as the separator.

[0091] (5) Assembling the battery:

[0092] The positive electrode sheet, separator and negative electrode sheet prepared above are stacked in sequence, so that the separator is placed between the positive and negative electrode sheets to play a role of isolation. Then, they are wrapped with aluminum plastic film, transferred to a vacuum oven for drying at 120°C, and sealed after injecting 3.0g / Ah of electrolyte. After standing, hot and cold pressing, formation, clamping, capacity division and other processes, a soft-pack battery (i.e., lithium-ion battery) with a capacity of 1Ah is finally prepared.

[0093] The specific steps and conditions for electrolyte formation are as follows: after the electrolyte is injected, maintain a hot pressure environment of 0.1MPa, charge at 0.02C for 17min at 45°C in a static state, stand for 5min and then charge to 0.3Ah at 0.02C, then cut off the air bag and vacuum seal, and stand at room temperature for 48h to complete the electrolyte formation.

[0094] Example 2

[0095] The difference between this embodiment and embodiment 1 is that when preparing the negative electrode plate, in step S1, a first negative electrode material with a structural stability parameter S1 of 7.4 and an average particle size Dv50 of 13.7 μm is used.

[0096] In the negative electrode sheet obtained in this embodiment, the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer in the negative electrode active material layer is 3.2, and the negative electrode active material layer It is 30.4.

[0097] Example 3

[0098] The difference between this embodiment and embodiment 1 is that when preparing the negative electrode plate, in step S1, a first negative electrode material with a structural stability parameter S1 of 10.4 and an average particle size Dv50 of 12.2 μm is used.

[0099] In the negative electrode sheet obtained in this embodiment, the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer in the negative electrode active material layer is 3.2, and the negative electrode active material layer It is 26.7.

[0100] Example 4

[0101] The difference between this embodiment and embodiment 1 is that: when preparing the negative electrode sheet, in step S1 and step S2, a first negative electrode material with a structural stability parameter S1 of 8.3 and an average particle size Dv50 of 13.3 μm and a second negative electrode material with a structural stability parameter S2 of 1.2 and an average particle size Dv50 of 18.3 μm are used; in step S3, after coating the negative electrode active material layer on the current collector, the compaction density of the negative electrode active material layer on the current collector is adjusted to 1.75 g / m 3 .

[0102] In the negative electrode sheet obtained in this embodiment, the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer in the negative electrode active material layer is 6.9, and the negative electrode active material layer It is 49.0.

[0103] Example 5

[0104] The difference between this embodiment and embodiment 1 is that: when preparing the negative electrode sheet, in step S1 and step S2, a first negative electrode material with a structural stability parameter S1 of 8.0 and an average particle size Dv50 of 16.2 μm and a second negative electrode material with a structural stability parameter S2 of 100 and an average particle size Dv50 of 18.0 μm are used; in step S3, after coating the negative electrode active material layer on the current collector, the compaction density of the negative electrode active material layer on the current collector is adjusted to 1.75 g / m 3 .

[0105] In the negative electrode sheet obtained in this embodiment, the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer in the negative electrode active material layer is 6.9, and the negative electrode active material layer It is 71.2.

[0106] Example 6

[0107] The difference between this embodiment and embodiment 1 is that: when preparing the negative electrode sheet, in step S1 and step S2, a first negative electrode material with a structural stability parameter S1 of 15.6 and an average particle size Dv50 of 11.2 μm and a second negative electrode material with a structural stability parameter S2 of 1.2 and an average particle size Dv50 of 18.3 μm are used; in step S3, after coating the negative electrode active material layer on the current collector, the compaction density of the negative electrode active material layer on the current collector is adjusted to 1.75 g / m 3 .

[0108] In the negative electrode sheet obtained in this embodiment, the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer in the negative electrode active material layer is 13.0, and the negative electrode active material layer It is 64.7.

[0109] Example 7

[0110] The difference between this embodiment and embodiment 6 is that when preparing the negative electrode plate, in step S1, a first negative electrode material with a structural stability parameter S1 of 13.4 and an average particle size Dv50 of 12.6 μm is used.

[0111] In the negative electrode sheet obtained in this embodiment, the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer in the negative electrode active material layer is 11.2, and the negative electrode active material layer It is 56.8.

[0112] Example 8

[0113] The difference between this embodiment and embodiment 1 is that: when preparing the negative electrode sheet, in step S1 and step S2, a first negative electrode material with a structural stability parameter S1 of 9.7 and an average particle size Dv50 of 13.1 μm and a second negative electrode material with a structural stability parameter S2 of 2.3 and an average particle size Dv50 of 16.7 μm are used; in step S3, after the negative electrode active material layer is coated on the current collector, the compaction density of the negative electrode active material layer on the current collector is adjusted to 1.75 g / m 3 .

[0114] In the negative electrode sheet obtained in this embodiment, the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer in the negative electrode active material layer is 4.2, and the negative electrode active material layer It is 86.3.

[0115] Example 9

[0116] The difference between this embodiment and embodiment 1 is that: when preparing the negative electrode sheet, in step S1 and step S2, a first negative electrode material with a structural stability parameter S1 of 1.51 and an average particle size Dv50 of 13.7 μm and a second negative electrode material with a structural stability parameter S2 of 1.2 and an average particle size Dv50 of 18.3 μm are used; in step S3, after coating the negative electrode active material layer on the current collector, the compaction density of the negative electrode active material layer on the current collector is adjusted to 1.75 g / m 3 .

[0117] In the negative electrode sheet obtained in this embodiment, the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer in the negative electrode active material layer is 12.6, and the negative electrode active material layer It is 91.2.

[0118] The negative electrode sheets prepared in Examples 1 to 9 were subjected to material parameter tests, and the secondary lithium-ion batteries equipped with the negative electrode sheets prepared in Examples 1 to 10 were subjected to fast charge time tests, cycle capacity retention rate tests, and storage performance tests.

[0119] (1) Structural stability parameter S test of negative electrode materials:

[0120] Referring to the national standard GB / T24533-2019, the powder sample is pressed into a tablet. Before the test, the standard pressure of 2T is maintained for 20S. The formal operation starts after a pressure relief interval of 10min. The 5T powder pressure is measured as P0, and then the powder is tested at 2.5T, 3T, 3.5T...2+0.5nT...pressures. The compactions are recorded as P1, P2, P3...Pn..., respectively. When Pn / Pn-1≥1.05, this Pn is called the particle structure failure compaction, and the structural stability parameter S=2+0.5n / 5 is recorded.

[0121] (2) Porosity ε test of negative electrode sheet:

[0122] Referring to the test method of national standard GB21650.1-2008, a small number of negative electrode plates were selected for testing.

[0123] (3) Test of tortuosity τ of negative electrode:

[0124] The test was performed with reference to the image method used in the literature Ebner M, Wood V. Tool for Tortuosity Estimation in Lithium Ion Battery Porous Electrodes[J]. Journal of the Electrochemical Society, 2014, 162(2): A3064-A3070.

[0125] (4) Orientation degree V of negative electrode sheet OI test:

[0126] According to the national standard GB / T23442-2009, a small number of negative electrode pieces were selected for testing, and the intensity ratio of the I004 / I110 peak in the XRD diffraction of the negative electrode pieces was taken as the orientation degree V OI .

[0127] (5) Fast charging time test:

[0128] The battery cell is directly charged to 8% SOC state with 0.33C current, and then the charging windows of 10%, 20%, 30%, 40%, 50%, 60%, 70%, and 80% are tested according to the three-electrode window of the battery cell, which are C1, C2, C3, C4, C5, C6, C7, and C8 respectively. Step charge is used to charge to 80%, that is, 8%-10% is charged with C1, 10% to 20% is charged with C2, and so on. The charging time from 8% to 80% SOC state is recorded as the fast charging capability measurement standard. The calculation formula is

[0129] T=(0.02 / C1+0.1 / C2+0.1 / C3+0.1 / C4+0.1 / C5+0.1 / C6+0.1 / C7+0.1 / C8)×60.

[0130] (6) Cycle capacity retention test:

[0131] At 25°C, the battery cell is charged and discharged at 0.21A / g (calculated based on the mass of the positive electrode material) and 2.8-4.25V. The number of cycles when the initial capacity reaches 80% is recorded as the material cycle capacity evaluation number.

[0132] (7) Storage performance test:

[0133] At 25°C, the capacity is fixed with a current of 0.33C and recorded as C0. The battery cells are then stored at a high temperature of 60°C. After that, the battery cells are taken out every 7 days and the capacity is tested at room temperature and recorded as C1, C2, ... Cn. The number of days when Cn deteriorates to 80% of C0 is recorded as a measure of storage capacity.

[0134] The preparation parameters of the negative electrode plates in Examples 1 to 9 are shown in Tables 1 and 2, and the performance test results of the negative electrode plates in secondary lithium batteries are shown in Table 3.

[0135] Table 1: Parameters of negative electrode materials used in preparing negative electrode sheets in Examples 1 to 9

[0136]

[0137] Table 2: Material parameters of negative electrode sheets prepared in Examples 1 to 9

[0138]

[0139] Table 3: Fast charging performance, cycle discharge performance and storage performance of secondary lithium-ion batteries prepared with negative electrode sheets of assembly examples 1 to 9

[0140]

[0141] It can be seen from the test results of Examples 1 to 9 that the structural parameters of the negative electrode active material layer in the negative electrode sheet are adjusted so that the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer in the negative electrode active material layer is 0.01-10.0 and satisfies At the same time, the fast charging performance, cycle performance and storage performance of secondary lithium-ion batteries can be improved.

[0142] It can be seen from the test results of Examples 1 to 3 that when the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer in the negative electrode active material layer is 0.1-5.0 and satisfies The secondary lithium-ion battery has good fast charging performance, cycle performance and storage performance at the same time. The fast charging time of the secondary lithium-ion battery to 80% SOC can be reduced to less than 15 minutes, the number of cycles to maintain 80% capacity is more than 3000 cycles, and the number of days to maintain 80% storage capacity is more than 210 days.

[0143] Comparing the test results of Examples 1 to 3 and Examples 4 to 5, it can be seen that when the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer in the negative electrode active material layer is lower than 0.1 or higher than 5.0, it will lead to the negative electrode plate being adjusted by compaction and plate design. The effect of improving the fast charging performance, cycle performance and storage performance of secondary lithium-ion batteries is not obvious. As shown in the test results, the fast charging time of secondary lithium-ion batteries to 80% SOC is increased to more than 15 minutes, the number of cycles to maintain 80% capacity is reduced to 1700 to 2100 cycles, and the number of days to maintain 80% storage capacity is also reduced to less than 210 days.

[0144] By comparing the test results of Examples 1 to 5 and Examples 6 to 7, it can be seen that when the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer materials in the negative electrode active material layer is higher than 10.0, the fast charging performance, cycle performance and storage performance of the secondary lithium ion battery will be further reduced. As shown in the test results, with the increase of S1 / S2 in the negative electrode plate, the fast charging time of the secondary lithium ion battery to 80% SOC is further increased on the basis of 15 minutes, the number of cycles to maintain 80% capacity is further reduced on the basis of 1700 cycles, and the number of days at which 80% storage capacity is maintained is further reduced to less than 170 days.

[0145] Comparing the test results of Examples 1 to 4 and Example 8, it can be seen that when the negative electrode active material layer When the structure stability parameter ratio S1 / S2 of the first active material layer and the second active material layer materials is in the range of 0.1-5.0, the fast charging performance, cycle performance and storage performance of the secondary lithium-ion battery will be greatly reduced. As shown in the test results, the fast charging time of the secondary lithium-ion battery to 80% SOC is increased to more than 18 minutes, the number of cycles to maintain 80% capacity is reduced to less than 1400 cycles, and the number of days to maintain 80% storage capacity is reduced to less than 140 days.

[0146] Comparing the test results of Example 8 and Example 9, it can be seen that when the negative electrode active material layer When the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer materials is higher than 10.0, the fast charging performance, cycle performance and storage performance of the secondary lithium-ion battery will further decline significantly. As shown in the test results, the fast charging time of the secondary lithium-ion battery to 80% SOC is further increased to more than 20 minutes, the number of cycles to maintain 80% capacity is further reduced to less than 1000 cycles, and the number of days to maintain 80% storage capacity is further reduced to less than 110 days.

[0147] In summary, the present invention provides a negative electrode sheet, which makes the negative electrode active material layer meet the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer of 0.01-10.0 by adjusting the double-layer material selection and overall compaction density of the negative electrode active material layer, and The ratio of the negative electrode to the negative electrode is 6.5-80.0, so as to adjust the structural stability of the negative electrode and the rationality of the pore distribution, and utilize the negative electrode to form a negative electrode active material layer with low tortuosity, high orientation and rich pores during compaction, thereby improving the fast charging, cycling and storage performance of the secondary lithium-ion battery.

[0148] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A negative electrode plate, characterized in that: include: current collector; A negative electrode active material layer, the negative electrode active material layer is at least located on one side of the current collector, the negative electrode active material layer includes a first active material layer and a second active material layer, the first active material layer and the second active material layer are stacked in a direction close to the current collector; Wherein, the structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer satisfies 0.01-10.

0.

2. The negative electrode sheet according to claim 1, characterized in that: The negative electrode material in the negative electrode active material layer includes a graphite material.

3. The negative electrode sheet according to claim 1, characterized in that: The structural stability parameter ratio S1 / S2 of the first active material layer and the second active material layer satisfies 0.1-5.

0.

4. The negative electrode sheet according to claim 1, characterized in that: The structural stability parameter S1 of the first active material layer is 3-16.

5. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active material layer satisfies Wherein, τ is the tortuosity of the negative electrode active material layer, ε is the porosity of the negative electrode active material layer, P is the compaction density of the negative electrode active material layer, V OI It is the stacking orientation degree of the negative electrode material particles in the negative electrode active material layer.

6. The negative electrode sheet according to claim 5, characterized in that: The negative electrode active material layer satisfies 7. The negative electrode sheet according to claim 1, characterized in that: The compaction of the negative electrode active material layer is 1.65-1.75 g / cm 3 .

8. A method for preparing the negative electrode sheet according to claims 1 to 7, characterized in that: include: Mixing the first negative electrode material with a binder, a conductive agent and a thickener to form a slurry to obtain a first active material layer slurry; Mixing the second negative electrode material with a binder, a conductive agent and a thickener to form a slurry to obtain a second active material layer slurry; The second active material layer slurry and the first active material layer slurry are sequentially coated on at least one side of the current collector, and after coating, the negative electrode sheet is obtained by drying, compacting, die-cutting and punching; Wherein, the hardness of the first negative electrode material is higher than that of the second negative electrode material.

9. The method for preparing a negative electrode sheet according to claim 8, characterized in that: The structural stability parameter ratio S1 / S2 of the first negative electrode material and the second negative electrode material satisfies 0.01-10.

0.

10. The method for preparing a negative electrode sheet according to claim 8, characterized in that: The average particle size Dv50 of the first negative electrode material is 11-17 μm, and the average particle size Dv50 of the second negative electrode material is 16-19 μm.

11. An electrochemical device, characterized in that: It comprises a positive electrode sheet, a separator, an electrolyte and a negative electrode sheet as claimed in any one of claims 1 to 7.

Citation Information

Cited By

  • Secondary battery and electronic device

    WO2026183851A1